PENGARUH IKLIM KERJA TERHADAP KEPUASAN KERJA PEGAWAI DI KEPOLISIAN DAERAH (POLDA) - Edwin Tampubolon; Dea Okviar Egano Napitupulu; Muhammad Syafri Umri; Solli Maarip Pangaribuan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
Employee job satisfaction is an important factor because it affects the operations of the entire organization. The satisfaction felt by employees at work shows that they have a pleasant feeling in carrying out work tasks. Job satisfaction is also a positive attitude of employees towards various situations in the workplace.